PENERAPAN ORGANISASI BELAJAR DI UNIVERSITAS NEGERI SURABAYA MENUJU BADAN HUKUM PERGURUAN TINGGI (BHPT) - Martadi Martadi (Perspektif Ilmu Pendidikan, 2009)
This study is aimed at finding out how State University o Surabaya implemented learning organization principles in developing itself to be a BHPT, an independent state university. Desribing the development of this institution as from its establishment till it changed to be a university, the study looked at the process as learning activities. Apllying the organization learning theory, the study made thorough analysis of the process adn gave a set of recommendation for further consideration in the university development.